2014
DOI: 10.1021/jf500106r
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Antioxidant Activity of Dietary Supplements from Pomegranate, Milk Thistle, Green Tea, Grape Seed, Goji, and Acai: Effects of in Vitro Digestion

Abstract: The antioxidant activity (AA) of fruits and vegetables has been thoroughly investigated but less is known about the AA of dietary supplements (DS). We therefore assessed the AA of three to five DS each from pomegranate, milk thistle, green tea, grapes, goji, and acai using four widely used standard methods. The secondary objective was to determine the effects of in vitro digestion on their AA. The AA of the DS prior to digestion ranked as follows: pomegranate > resveratrol > green tea > grape seed > milk thist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 39 publications
3
26
0
2
Order By: Relevance
“…A possible reason of varying bioaccessibility of antioxidant capacity values could be associated with several factors related to the process conditions, chemical interactions with other phytochemicals, biomolecules present in the food and also the protocols used for the measurements (Parada and Aguilera, 2007). In agreement with our data, Henning et al (2014) reported a 21.5% and 8.1% decrement of TEAC (trolox equivalent antioxidant capacity) in green tea and grape seed samples during in vitro simulated digestion. In another study, Değirmencioğlu et al (2016) concluded DPPH bioaccessibilities of fermented vegetable juices between 16-32%.…”
Section: Antioxidant Capacitysupporting
confidence: 88%
“…A possible reason of varying bioaccessibility of antioxidant capacity values could be associated with several factors related to the process conditions, chemical interactions with other phytochemicals, biomolecules present in the food and also the protocols used for the measurements (Parada and Aguilera, 2007). In agreement with our data, Henning et al (2014) reported a 21.5% and 8.1% decrement of TEAC (trolox equivalent antioxidant capacity) in green tea and grape seed samples during in vitro simulated digestion. In another study, Değirmencioğlu et al (2016) concluded DPPH bioaccessibilities of fermented vegetable juices between 16-32%.…”
Section: Antioxidant Capacitysupporting
confidence: 88%
“…A recent work evaluated the effect of in vitro digestion on the antioxidant activity of dietary supplements from pomegranate, milk thistle, green tea, grape seed, goji and acai, all of them as extracts. The authors found that, except for green tea and grape extracts, no significant losses of antioxidant activities occurred during in vitro digestion (Henning et al, 2014).…”
Section: Effects Of In Vitro Digestion and Colonic Fermentation On Thmentioning
confidence: 97%
“…Other studies on the impact of digestion, in vitro , on antioxidant capacity/activity and/or total phenolic content reported a decrease in fruit beverages [84], either no change or a decrease for herbal teas, prepared from infusions of powdered herbs [85] or either decreases, increases or no statistically significant change for dietary antioxidant supplements [86]. The type of in vitro model ( i.e.…”
Section: The Impact Of Processes Prior To and Post Consumption Onmentioning
confidence: 99%